EDUCATION TECHNOLOGY INNOVATION: ENHANCING THE ACADEMIC PERFORMANCE OF UNDERGRADUATE DISTANCE LEARNERS IN NIGERIA UNIVERSITIES THROUGH MASSIVE OPEN ONLINE COURSES (MOOCS) - Charles N Ohanyelu (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The research investigates the possible impacts of Massive Open Online Courses (MOOCs) on the academic performance of undergraduate distance learners in Nigerian universities. Given the abundance of information available in our digital age, technology plays a crucial role in educational advancement, making it possible for students to learn using computers and portable devices with internet connectivity. This educational advancement has created both opportunities and challenges in the way students’ learning is structured in the twenty-first century. In contrast to the usual traditional methods of teaching and learning employed a few years ago, the trend has brought about a number of innovations that create new learning opportunities. In light of this context, MOOCs were created to alleviate the difficulties encountered by students who are balancing work and study. Two (2) research questions and a hypothesis were examined, utilizing a survey questionnaire as the data collection tool. The respondents comprised 278 randomly selected undergraduate students currently enrolled in distance learning programmes at universities in Nigeria. The result shows a positive and significant correlation between students’ academic performance and MOOCs. This study therefore concludes that the implementation of Massive Open Online Courses (MOOCs) in distance learning education will significantly improve the academic performance of undergraduate students in Nigerian universities.